Performance Enhancement of Dye Sensitized Solar Cell (DSSC) through TiO2/rGO Hybrid: Comprehensive Study on Synthesis and Characterization - Hatib, Rustan; Anwar, Khairil; Magga, Ramang; Astak, Muh Anjas; Widhiyanuriyawan, Denny; Wardoyo, Wardoyo (Universitas Negeri Malang, 2024)
The TiO2 film is immersed in a graphite oxide solution, preparing it for thermal reduction, which converts the graphite oxide to reduced graphene oxide (rGO). This process produces rGO hybrid TiO2 photoanodes for dye-sensitized solar cells (DSSC). rGO in the TiO2 structure prevents electron recombination and improves overall efficiency. The main advantage of this method is its ability to prevent loss of rGO during the sintering process, which is a common problem with other methods. The study investigated heating temperatures ranging between 300˚C, 350˚C, 400˚C, 450˚C, and 500˚C to determine optimal conditions. The presence of rGO in the photoanode structure was confirmed via X-ray diffraction and Fourier transform infrared spectroscopy analysis. JV (current-voltage density) measurements of DSSC based on TiO2/rGO photoanode revealed that the highest photoelectric conversion efficiency (0.1923%) was achieved at 400˚C, much higher than other temperature variations. The findings demonstrate the effectiveness of a simple low-temperature thermal reduction process in producing graphene suitable for semiconductor applications in DSSC. The RGO produced through this method not only improves energy conversion efficiency but also outperforms traditional graphite electrodes. By optimizing the thermal reduction process and fine-tuning the heating conditions, this study advances the practical application of graphene-based materials in solar cell technology. This method overcomes the loss of rGO during sintering, ensuring its beneficial properties are retained. Overall, this study shows that low-temperature thermal reduction is an efficient technique to improve DSSC performance through the incorporation of reduced graphene oxide.